ANALISIS DAN PERUMUSAN STRATEGI MARKETING UNTUK MENINGKATKAN BRAND AWARENESS PRODUK ICE CREAM NEW ZEALAND NATURAL - Angeline Angeline; Irma Patrisia2; Putri Ramadhyta; Bun Sucento (Journal of Business Strategy and Execution, 2008)
Ice cream is a favorite’s snack for all ages. Societies are willing to spend their money to have premium ice cream. They are willing to buy premium ice cream at quite expensive prices.  Nowadays many brands of premium ice cream are introduced in the market and cause the competition to be tighter. Because of that, effort to keep the new customers is more important then to collect the new customers. Ice cream companies spend extra efforts to develop customer’s satisfaction for getting customer loyalty. In facing the tight competition in this industry, an ice cream company that produces ice cream with the brand of New Zealand Natural formulates a marketing strategy to develop brand awareness. The analysis in this study is based on five competitive forces analysis, marketing mix, and STP. Finally, this study also advances some suggestions to improve the strategy.